2011
DOI: 10.1097/bsd.0b013e3181dc9969
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With Chronic Low Back Pain Likely to Benefit From Lumbar Facet Radiofrequency Denervation

Abstract: Rhizolysis is a valuable tool for the symptomatic treatment of chronic lumbar facet joint pain. A meticulous selection of patients using a combination of clinical history, examination, imaging tests, and lumbar facet joint block with a local anesthetic, achieves long-lasting results by helping reduce the impact on these patients' daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
2
17
0
3
Order By: Relevance
“…This was followed by several studies to establish the efficiency of such technique in management of lumbar facet pain. The effectiveness of RF has been supported by four randomized, prospective controlled trials . They showed that lumbar facet denervation was more effective than sham treatment.…”
Section: Discussionmentioning
confidence: 98%
“…This was followed by several studies to establish the efficiency of such technique in management of lumbar facet pain. The effectiveness of RF has been supported by four randomized, prospective controlled trials . They showed that lumbar facet denervation was more effective than sham treatment.…”
Section: Discussionmentioning
confidence: 98%
“…RF or PRF to the facet intra-articular or dorsal medial division, are used to control the pain stemming from the lumbar facet arthropathy. [ 25 26 27 ] Felix berjemo conducted a study using conventional RF for 80 C0, 90 s, on 86 patients and opened the 1 year follow-up findings to discussion. They found the start-up ODI value as 18.93 in average, and reported lower in the 3 rd month as 8.8; in the 6 th month as 9.66; and in the 12 th month as 12.2.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were satisfied at a rate of 75.67%, and the back pains were relieved in 66% in 6 months; and 50% in 1 year. [ 27 ] In another study conducted on 81 patients, it was determined that the RF group was more efficient when compared to the control Group. [ 28 ] The PRF, which has been used in more recent times, causes less neuropathic pain because it is a more neuroprotective method than the conventional RF.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] These conflicting findings suggest a strong need to better identify treatment responders. [9][10][11][12][13] The use of "control" injections is frequently advocated to improve RF treatment outcomes, the rationale being that uncontrolled medial branch (facet joint nerve) blocks (MBBs) are associated with a high false-positive rate. 14,15 Numerous researchers and organizations have recommended the use of controlled injections as a means to reduce the high false-positive rate of diagnostic MBB and to improve treatment results.…”
Section: Methods: a Multicenter Prospective Study Was Performed In 223mentioning
confidence: 99%